ANALISIS EFEKTIFITAS MEDIA PROMOSI TERHADAP PENERIMAAN MAHASISWA BARU (PMB) DI STIKES AL ISLAM YOGYAKARTA - Hidayati , Aini; Akhmad, Jazuli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
Competition between universities is now getting tougher, especially Yogyakarta has 136 units of higher education which has several categories including academic, polytechnic, high school, institute, and university. STIKES Al Islam is a private health college located in LLDIKTI region V. The number of students there are 79 students consisting of S1 and D3 nursing. Promotional media used by STIKES Al Islam are online media, print media, and others. In the last five years 2017 to 2021 the number of students enrolled did not match the specified target. The purpose of this study was to determine the promotion carried out, the factors that affect the ineffectiveness of promotional media. This type of research is descriptive qualitative with 8 informants consisting of students and the relevant PMB committee. The results of the study found that Instagram was the most accessed media by students who entered STIKES Al Islam. Factors that affect the ineffectiveness of promotional media, the marketing mix is not optimal, namely direct marketing, advertising, lack of marketing strategies, and less than optimal use of media for promotion.